ACL Deficiency Increases Forces on the Medial Femoral Condyle and the Lateral Meniscus with Applied Rotatory Loads. (19th October 2016) - McDonald, Lucas S.; Boorman-Padgett, James; Kent, Robert; Stone, Kyle; Wickiewicz, Thomas L.; Pearle, Andrew D.; Imhauser, Carl W.
Abstract : Background: The articular surfaces and menisci act with the anterior cruciate ligament (ACL) to stabilize the knee joint. Their role in resisting applied rotatory loads characteristic of instability events is unclear despite commonly observed damage to these intra-articular structures in the acute and chronic ACL injury settings. Methods: Ten fresh-frozen human cadaveric knees were mounted to a robotic manipulator. Combined valgus and internal rotation torques were applied in the presence and absence of a 300-N compressive load. Forces carried by the individual menisci and via cartilage-to-cartilage contact on each femoral condyle in ACL-intact and ACL-sectioned states were measured using the principle of superposition. Results: In response to applied valgus and internal rotation torques in the absence of compression, sectioning of the ACL increased the net force carried by the lateral meniscus by at most 65.8 N (p < 0.001). Moreover, the anterior shear force carried by the lateral meniscus increased by 25.7 N (p < 0.001) and 36.5 N (p = 0.042) in the absence and presence of compression, respectively. In response to applied valgus and internal rotation torques, sectioning of the ACL increased the net force carried by cartilage-to-cartilage contact on the medial femoral condyle by at most 38.9 N (p = 0.006) and 46.7 N (p = 0.040) in the absence and presence of compression, respectively. Additionally, the lateral shear force carried by cartilage-to-cartilage contact on the medial femoral condyle increased by at most 21.0 N (p = 0.005) and by 28.0 N (p = 0.025) in the absence and presence of compression, respectively. Forces carried by the medial meniscus and by cartilage-to-cartilage contact on the lateral femoral condyle changed by <5 N as a result of ACL sectioning. Conclusions: ACL sectioning increased the net forces carried by the lateral meniscus and medial femoral condyle—and the anterior shear and lateral shear forces, respectively—in response to multiplanar valgus and internal rotation torque. Clinical Relevance: These loading patterns provide a biomechanical rationale for clinical patterns of intra-articular derangement such as lateral meniscal injury and osseous remodeling of the medial compartment seen with ACL insufficiency.